2004
DOI: 10.1016/j.ydbio.2004.05.030
|View full text |Cite
|
Sign up to set email alerts
|

PKC isotypes in post-activated and fertilized mouse eggs: association with the meiotic spindle

Abstract: Several isotypes of protein kinase C (PKC) have been reported to be expressed in mammalian eggs, but it is unknown whether these isotypes have a common function in the egg during or within the first few hours of fertilization. Here we show that the isotypes of PKC exhibit distinct patterns of enrichment immediately after mouse egg activation. PKCalpha and gamma accumulate in the egg cortex 25 min post-activation, while only PKCalpha accumulates at the contractile ring of the forming second polar body about 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…The Par proteins have been demonstrated to be crucial for polarity establishment in many cell types [Cowan and Hyman, 2004;Goldstein and Macara, 2007]. In mouse oocytes, PAR1, PAR4, and aPKC are localized to meiotic spindles [Baluch et al, 2004;Vinot et al, 2004;Duncan et al, 2005;Moore and Zernicka-Goetz, 2005;Szczepanska and Maleszewski, 2005;Na and Zernicka-Goetz, 2006]. aPKC accumulates at spindle poles and may play a role in regulating spindle MTs, as disruption of this distribution by Cdc42 perturbation results in abnormal spindle morphology [Na and Zernicka-Goetz, 2006].…”
Section: Establishment Of Cortical Polarity: the Chromatin Brings Thementioning
confidence: 99%
“…The Par proteins have been demonstrated to be crucial for polarity establishment in many cell types [Cowan and Hyman, 2004;Goldstein and Macara, 2007]. In mouse oocytes, PAR1, PAR4, and aPKC are localized to meiotic spindles [Baluch et al, 2004;Vinot et al, 2004;Duncan et al, 2005;Moore and Zernicka-Goetz, 2005;Szczepanska and Maleszewski, 2005;Na and Zernicka-Goetz, 2006]. aPKC accumulates at spindle poles and may play a role in regulating spindle MTs, as disruption of this distribution by Cdc42 perturbation results in abnormal spindle morphology [Na and Zernicka-Goetz, 2006].…”
Section: Establishment Of Cortical Polarity: the Chromatin Brings Thementioning
confidence: 99%
“…In this study, we further demonstrate from the GST pull-down assay that CagSpin directly or indirectly associates with h-tubulin, and therefore provide the first biochemical evidence for the specific interaction of Spindlin protein and h-tubulin, the microtubule component. Interestingly, some important proteins that play crucial functions during oocyte maturation and egg fertilization, such as p39 mos (Zhou et al, 1992;Haccard et al, 1993;Verlhac et al, 1996), p34 cdc2 of metaphase promoting factor (MPF) (Langan et al, 1989;Peter et al, 1990;Verde et al, 1990;Zhou et al, 1991Zhou et al, , 1992, cyclin B, the regulatory component of MPF (Pines and Hunter, 1991;Ookata et al, 1993), MAP kinase (Verlhac et al, 1993) and PKC (Page Baluch et al, 2004), have been also confirmed to associate with microtubules. Interestingly, three putative PKC phosphorylation sites have been revealed in the CagSpin sequence (Fig.…”
Section: Biochemical Evidence Of Association Between B-tubulin and Camentioning
confidence: 99%
“…Total PKC remained behind in the cytoskeleton after the detergent extraction process; the closeness of this binding was confirmed by FRET analysis between -tubulin of the meiotic spindle and the PKC isotypes. FRET analysis demonstrated a close molecular proximity not only between -tubulin and PKC , but also between -tubulin and PKC (Baluch et al, 2004, Baluch & Capco, 2008. Other investigations have shown that PKC exists in the cytoplasm of the fertilization-competent egg (Raz et al, 1998).…”
Section: Oocytes and Eggsmentioning
confidence: 74%
“…Total antibody, that is, antibody that detects both the phosphorylated and unphosphorylated form of the kinase, directed against PKC , -, -and -were found not only in the cytoplasm, but also enriched on the spindle apparatus of the fertilization-competent egg (Baluch et al, 2004). The tightness of this PKC binding was assessed by detergent extraction, a process which removes the soluble components of the cell and retains the egg's cytoskeleton and associated proteins.…”
Section: Oocytes and Eggsmentioning
confidence: 99%
See 1 more Smart Citation